2020
DOI: 10.1177/10925872211019731
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of GIS for Identifying Areas of Recreation Conflict for Targeted Interpretive Messaging

Abstract: Past research has extensively studied interpretive messaging and visitor conflict within parks and protected areas. However, comprehensive understanding of how to identify trailside interpretive sign locations is lacking. The purpose of this study was to introduce an approach using geographic information systems (GIS) that supplements decision-making regarding sign placement. The study site was Grand Canyon National Park’s Rim to Rim (R2R) corridor. To identify sign placement locations, two analytical phases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Spatiotemporal information is important because every visitor experience occurs at a specific location and at a specific time (Aspers, 2006; Hägerstrand, 1970). By utilizing visitor travel pattern information, parks and protected area (PPA) managers can identify when and where visitors are moving, which can be helpful when planning what messages may be salient and where to place and concentrate interpretive efforts (D’Antonio & Monz, 2016; Peterson et al, 2021; Sharp et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Spatiotemporal information is important because every visitor experience occurs at a specific location and at a specific time (Aspers, 2006; Hägerstrand, 1970). By utilizing visitor travel pattern information, parks and protected area (PPA) managers can identify when and where visitors are moving, which can be helpful when planning what messages may be salient and where to place and concentrate interpretive efforts (D’Antonio & Monz, 2016; Peterson et al, 2021; Sharp et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Often researchers use Global Positioning System’s (GPS) such as GPS data loggers that are distributed to actual visitors to track actual visitor travel patterns which are then mapped using Geographic Information Systems (GIS; Peterson et al, 2021; Sharp et al, 2019). Prior studies have shown that visitor travel pattern information can be organized into numerous variables including total distance traveled, total duration of visit, and average speed (Beeco & Hallo, 2014) to gain a thorough understanding of movement trends and travel typologies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations